Droppin’ Knowledge on Race: Hip-Hop, White Adolescents, and Anti-Racism Education - Netcoh, Steven (Radical Teacher, 2013)
In this essay, the author examines how Hip-Hop can be mobilized in anti-racism educational initatives. The author claims that existing research on Hip-Hop and white adolescents suggests a negative corrleation between white youths’ engagement with Hip-Hop and their understanding of how race and racism function in American society. In response to this research, the author argues Hip-Hop’s diverse racial discourses and ideologies must be made the subject of direct and critical inquiry in secondary and post-secondary classrooms to maximize its democratic potential. The author outlines specific approaches for how teachers can employ Hip-Hop in anti-racism curricula in secondary and post-secondary classrooms. Collectively, the essay serves as a preliminary investigation of Hip-Hop pedagogies of race and whiteness.